The Mothers of Boate Kiss: Political, Social, and Rhetorical Considerations - Dunlap, Maggie (Brasiliana: Journal for Brazilian Studies, 2024)
The present article examines the overlapping political, social, and rhetorical functions of the category of “mother” in various contexts related to the January 2013 Boate Kiss fire in Santa Maria, Rio Grande do Sul, Brazil. Supported by theories of social suffering and ethnographies of violence, as well as poststructuralist notions of identity and gender, the analysis focuses on the medium-transcribed letters, newspaper articles, journalistic nonfiction, and social media posts related to two social movements that would coalesce among the affected in the tragedy’s aftermath: collectives for justice and groups ascribing to Kardecist Spiritism, both inscribed within the regional and national history of mothers in movements. Attending to gender also highlights the long-term political import of then-president Dilma Rousseff’s emblematic visit to Santa Maria on the day of the tragedy.